2021
DOI: 10.1016/j.ijbiomac.2021.08.232
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal IgA response elicited by intranasal immunization of Lactobacillus plantarum expressing surface-displayed RBD protein of SARS-CoV-2

Abstract: Coronavirus Disease 2019 (COVID-19) caused by a novel betacoronavirus SARS-CoV-2 has been an ongoing global pandemic. Several vaccines have been developed to control the COVID-19, but the potential effectiveness of the mucosal vaccine remains to be documented. In this study, we constructed a recombinant L. plantarum LP18:RBD expressing the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein via the surface anchoring route. The amount of the RBD protein was maximally expressed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…In particular, secretory IgA (S-IgA), located on the mucous membranes, plays a crucial role in mucosal immunity. In fact, this antibody can neutralize pathogens, particularly in respiratory tract infections caused by viruses, protecting the local mucosa from viral invasion [6]. SARS-CoV-2 infection results in a wide range of clinical signs, varying from asymptomatic to life-threatening acute respiratory distress syndrome, which is caused by a deleterious antiviral immune response in lungs [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, secretory IgA (S-IgA), located on the mucous membranes, plays a crucial role in mucosal immunity. In fact, this antibody can neutralize pathogens, particularly in respiratory tract infections caused by viruses, protecting the local mucosa from viral invasion [6]. SARS-CoV-2 infection results in a wide range of clinical signs, varying from asymptomatic to life-threatening acute respiratory distress syndrome, which is caused by a deleterious antiviral immune response in lungs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that antibodies in the respiratory tract or oral cavity could be important for protecting against other human respiratory viruses like SARS-CoV, influenza virus, and respiratory syncytial virus (RSV) [6,9]. Nevertheless, in the fight against COVID-19, most attention has been given to circulating virus-neutralizing antibodies, especially IgG and IgM [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Lactobacillus plantarum-based vaccine that expresses surface-displayed RBD of SARS-CoV-2 induced strong mucosal IgA (in respiratory and intestinal tracts) after IN immunization. 79 Further investigation is desired to evaluate bacterium-based vaccines’ immunogenicity and safety in bigger animal models to promote their clinical translation.…”
Section: Recent Progress In the Development Of Intranasal Covid-19 Vaccinesmentioning
confidence: 99%
“…PgsA-Spike (S) protein segments SA (residues 2 to 114) and SB (residues 264 to 596) of SARS-CoV [88] Lactobacillus plantarum Mycobacterium tuberculosis, Fusion antigen AgE6 [89] Lactobacillus plantarum SARS-CoV-2 Spike protein (whole protein) [90] Lactobacillus plantarum Receptor-binding domain (RBD) of the SARS-CoV-2 Spike protein [91] Novel vector host Francisella tularensis subsp. holarctica (single live multideletional attenuated) SARS-CoV-2 Spike, envelope, membrane, and nucleocapsid proteins [92] Mycobacterium paragordonae Receptor-binding domain (RBD) of the SARS-CoV-2 Spike protein [93] In recent years, various gastrointestinal disease-causing bacteria have been tested as live-attenuated mucosal-delivery vaccine systems.…”
Section: Lactobacillus Caseimentioning
confidence: 99%